Reading Strategies among ESL Malaysian Secondary School Students - Semry Anak Semtin; Mahendran Maniam (International Journal of Evaluation and Research in Education (IJERE), 2015)
This study aims to investigate the types of cognitive and metacognitive reading strategies employed by secondary school students in Malaysia to improve their comprehension. It uses a mixed-method approach which involves the instruments of a questionnaire and an interview. This study was conducted at SMK Kapit, involving ninety Form 4 students. Based on the findings, the students had used various reading strategies. The use of particular reading strategies is implied as their autonomous learning efforts to become more proficient readers. However, according to the frequency scales of strategy use (Oxford, 1990), the findings from the questionnaire indicate that most of the reported reading strategies have a mean between 2.5 and 3.49 as the students sometimes use these reading strategies. This revealed their lack of awareness of practising these reading strategies. Thus, teachers play a vital role in training students on the reading strategy use in order to enhance the effectiveness of their reading.